Developing a Delphi Validated Instrument for Assessing Digital Forensics Readiness Based on COBIT 2019 - Rochmadi, Tri; Fadlil, Abdul; Riadi, Imam (Indonesian Scientific Journal, 2025)
The increasing complexcity of cyber threats has reinforced the need for robust digital forensic readiness in higher education institutions. However, existing frameworks often lack integration between forensic capabilities and IT governance practices. Objective: This study aims to develop and validate a new instrument to assess digital forensic readiness based on the COBIT 2019 framework. Methods: A three-round Delphi process was conducted with seven digital forensics and IT governance experts to develop and validate a new instrument comprising forty proposed indicators across six domains. Result : The instrument achieved full context, with I-CVI values increasing from 0.60 to 0.99 and IQR values reaching 1.00 across all items. Implications: The validated instrument integrates governance and forensic principles, providing a standardized tool for institutional self-assessment and policy development, while contributing methodologically through the use of a structured Delphi validation process.